IDREAM: industrial Detector of REactor Antineutrinos for Monitoring at Kalinin nuclear power plant. (1st September 2022) - Abramov, A.; Chepurnov, A.; Etenko, A.; Gromov, M.; Konstantinov, A.; Kuznetsov, D.; Litvinovich, E.; Lukyanchenko, G.; Machulin, I.; Murchenko, A.; Nemeryuk, A.; Nugmanov, R.; et al.
Abstract: The paper is devoted to the description of the iDREAM detector and its systems. iDREAM is a prototype detector designed to demonstrate the feasibility of antineutrino detectors for remote reactor monitoring and safeguard purposes. Antineutrinos are detected with a 1 ton liquid scintillator via inverse beta decay on protons. In order to suppress cosmic muons, gamma and neutron background, the detector is housed in a dedicated shielding. The detector is installed at the Kalinin nuclear power plant (Russia), 20 m from the 3 GWth reactor core.